2021
DOI: 10.1536/ihj.20-564
|View full text |Cite
|
Sign up to set email alerts
|

Splenic Volume Index Determined Using Computed Tomography upon Admission Is Associated with Readmission for Heart Failure Among Patients with Acute Decompensated Heart Failure

Abstract: The spleen is associated with inflammation, and the size of the spleen is affected by hemodynamic congestion and sympathetic stimulation. However, the association between splenic size and prognosis in patients with heart failure remains unknown. Between January 2015 and March 2017, we analyzed 125 patients with acute decompensated heart failure who were assessed by computed tomography (CT) on the day of admission. The spleen was measured by 3-dimensional CT and then the patients were assigned to groups accordi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 34 publications
1
2
0
Order By: Relevance
“…Our study featured elderly Japanese patients, and it is worth acknowledging that the generalizability of our findings, especially with regard to the absolute values and the determination of the SVI cutoff points, to other patient populations remains uncertain. In this study, the SVI values displayed a wide range, akin to previous cohorts involving heart failure, likely attributable to the diversity of hemodynamic profiles [21,28] For example, in a recent study involving a stable heart failure cohort, the median SVI was 68.9 mL/m 2 , which was almost similar to our cohort [21].…”
Section: Splenic Sizesupporting
confidence: 71%
See 1 more Smart Citation
“…Our study featured elderly Japanese patients, and it is worth acknowledging that the generalizability of our findings, especially with regard to the absolute values and the determination of the SVI cutoff points, to other patient populations remains uncertain. In this study, the SVI values displayed a wide range, akin to previous cohorts involving heart failure, likely attributable to the diversity of hemodynamic profiles [21,28] For example, in a recent study involving a stable heart failure cohort, the median SVI was 68.9 mL/m 2 , which was almost similar to our cohort [21].…”
Section: Splenic Sizesupporting
confidence: 71%
“…In contrast, a different study, which included patients with decompensated heart failure, found that a higher SVI was associated with systemic congestion and subsequently a higher rate of heart failure recurrence [28]. These differing findings further underscore the complexity of the relationship between the SVI and clinical outcomes, which can be influenced by the specific patient population and clinical context under investigation [28].…”
Section: Prognostic Impact Of Higher Svimentioning
confidence: 99%
“…The spleen correlated with the inflammation closely, and hemodynamic congestion, and sympathetic stimulation would affect the size of the spleen (Maeda et al, 2021 ). However, the inflammation mechanisms require more investigation.…”
Section: Neuroimmune Regulation In Central-peripheral Crosstalkmentioning
confidence: 99%